2013
DOI: 10.1167/iovs.13-12702
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Foveal Cone Outer Segment Tips Line and Visual Recovery After Epiretinal Membrane Surgery

Abstract: The recovery of the foveal COST line defect is correlated with the BCVA after ERM surgery. The length of the preoperative COST line defect can predict the potential foveal function. (ClinicalTrials.gov number, NCT01549249.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 34 publications
1
86
2
9
Order By: Relevance
“…[20][21][22] Kim et al reported that the preoperative integrity of foveal photoreceptors may be an important prognostic factor for visual outcome in patients with idiopathic ERM. 20 Itoh et al 21 found that the recovery of the foveal photoreceptor cone outer segment tips line disintegrity is associated with the visual recovery after ERM surgery. In addition, the presence of a preoperative intact IS/OS junction was found to be an important predictor of better visual outcome following ERM surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Kim et al reported that the preoperative integrity of foveal photoreceptors may be an important prognostic factor for visual outcome in patients with idiopathic ERM. 20 Itoh et al 21 found that the recovery of the foveal photoreceptor cone outer segment tips line disintegrity is associated with the visual recovery after ERM surgery. In addition, the presence of a preoperative intact IS/OS junction was found to be an important predictor of better visual outcome following ERM surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The diameters of the IS/OS junction defect and ELM defect were measured when the absence of those parameters was detected. 15 Two masked investigators (SJ, JB) interpreted the OCT images. When there was disagreement, the third investigator was consulted for the final decision (WKL).…”
Section: Patients and Clinical Data Acquisitionmentioning
confidence: 99%
“…[35][36][37][38] These are all included in one category as distinguishing between them was inconsistent between observers. We differentiated subretinal fluid from more subtle outer retinal changes and also from outer retinal dehiscence seen in impending macular holes.…”
Section: Figure 1 Schematic Representation Of the Focal Vmt Classificmentioning
confidence: 99%